Lipid Ligands and Allergenic LTPs: Redefining the Paradigm of the Protein-Centered Vision in Allergy - Gonzalez-Klein, Zulema; Pazos-Castro, Diego; Hernandez-Ramirez, Guadalupe; Garrido-Arandia, Maria; Diaz-Perales, Araceli; Tome-Amat, Jaime (Frontiers in Allergy, 2022)
Lipid Transfer Proteins (LTPs) have been described as one of the most prevalent and cross-reactive allergen families in the general population. They are widely distributed among the plant kingdom, as well as in different plant organs ranging from pollen to fruits. Thus, they can initiate allergic reactions with very different outcomes, such as asthma and food allergy. Several mouse models have been developed to unravel the mechanisms that lead LTPs to promote such strong sensitization patterns. Interestingly, the union of certain ligands can strengthen the allergenic capacity of LTPs, suggesting that not only is the protein relevant in the sensitization process, but also the ligands that LTPs carry in their cavity. In fact, different LTPs with pro-allergenic capacity have been shown to transport similar ligands, thus positioning lipids in a central role during the first stages of the allergic response. Here, we offer the latest advances in the use of experimental animals to study the topic, remarking differences among them and providing future researchers a tool to choose the most suitable model to achieve their goals. Also, recent results derived from metabolomic studies in humans are included, highlighting how allergic diseases alter the lipidic metabolism toward a pathogenic state in the individual. Altogether, this review offers a comprehensive body of work that sums up the background evidence supporting the role of lipids as modulators of allergic diseases. Studying the role of lipids during allergic sensitization might broaden our understanding of the molecular events leading to tolerance breakdown in the epithelium, thus helping us to understand how allergy is initiated and established in the individuals.